eCM 2012
DOI: 10.22203/ecm.v024a05
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopy in the analysis of bacterial and eukaryotic cell footprints on implant surfaces

Abstract: We tested the suitability of two spectroscopic methods, x-ray photoelectron spectroscopy (XPS) and time of flight secondary ion mass spectrometry (ToF-SIMS), in the recognition of bacterial and eukaryotic cell footprints on implant surfaces. Human mesenchymal stem cells (MSCs) and Staphylococcus aureus were cultured on sample surfaces and detached using trypsin. Scanning electron microscopy confirmed that the processed surfaces did not contain any human or microbial cells. The footprints were then analysed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 60 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…For example, the zeta-potential for laser-ablated DLC was higher (-54.5±0.6 mV) 13 than for DLC film fabricated using filtered pulsed arc discharge (-70.2±1.1 mV, both measured in 1mM KCl, pH 7) 15 . This will most likely be reflected also as differences in the surface chemistries between the two samples, which could then translate into different electrochemical behavior during cyclic 12 voltammetry.…”
Section: Dopaminequinone Can Undergo a Chemical Reaction By Intramolementioning
confidence: 91%
“…For example, the zeta-potential for laser-ablated DLC was higher (-54.5±0.6 mV) 13 than for DLC film fabricated using filtered pulsed arc discharge (-70.2±1.1 mV, both measured in 1mM KCl, pH 7) 15 . This will most likely be reflected also as differences in the surface chemistries between the two samples, which could then translate into different electrochemical behavior during cyclic 12 voltammetry.…”
Section: Dopaminequinone Can Undergo a Chemical Reaction By Intramolementioning
confidence: 91%
“…Identifying mono-, di-, oligo-, and polysaccharides spectroscopically is often important for understanding the properties of formulated products . X-ray core level spectroscopies are structurally incisive methods that are increasingly used for the analysis of interfacial species in complex products, devices, and biomaterials. The most commonly used variant, X-ray photoelectron spectroscopy (XPS), provides information on the chemical state of atoms through sensitivity to the local electron density variations caused by changes in chemical bonding, which lead to chemical shifts of core level binding energies, and interpretation can be complemented or enhanced with the results of density functional theory (DFT) calculations . Careful C 1s core level binding energy measurements by XPS of fructose, xylose, glucose, galactose, maltose, α-lactose, β-lactose, and cellulose have previously revealed that XPS is sensitive enough to distinguish mono-, di-, and polysaccharides…”
Section: Introductionmentioning
confidence: 99%
“…For example, diamond-like carbon resisted microbial attachment in static conditions compared to titanium and tantalum, and ta-C resisted protein attachment compared to platinum . The sensitivity of ta-C is usually not high enough for biological applications, but functionalization of the ta-C surface with different carbon allotropes, such as carbon nanotubes and nanofibers or nanodiamonds (ND), has shown great potential for the electrochemical detection of different biomolecules, such as DA, glutamate, and ascorbic acid .…”
mentioning
confidence: 99%